Selected Patients With Peritoneal Metastases From Breast Cancer May Benefit From Cytoreductive Surgery: The Results of a Multicenter Survey - Cardi, Maurizio; Pocard, Marc; Dico, Rea Lo; Fiorentini, Gianmaria; Valle, Mario; Gelmini, Roberta; Vaira, Marco; Pasqual, Enrico Maria; Asero, Salvatore; Baiocchi, Gianluca; Di Giorgio, Andrea; Spagnoli, Alessandra; et al. (Frontiers in Oncology, 2022)
Background. Even though breast cancer is the most frequent extra-abdominal tumor causing peritoneal metastases, clear clinical guidelines are lacking. Our aim is to establish whether cytoreductive surgery (CRS) could be considered in selected patients with peritoneal metastases from breast cancer (PMBC) to manage abdominal spread and allow patients to resume or complete other medical treatments. Methods. We considered patients with PMBC treated in 10 referral centers from January 2002 to May 2019. Clinical data included primary cancer characteristics (age, histology, TNM), and data on metastatic disease (interval between primary BC and PM, molecular sub-type, other metastases, peritoneal spread). Overall survival (OS) was estimated using the Kaplan-Meier method. Univariate and multivariable data for OS were analyzed using the Cox proportional hazards model. Results. Of the 49 women with PMBC, 20 were treated with curative aim (CRS with or without HIPEC) and 29 with non-curative procedures. The 10-year OS rate was 27%. Patients treated with curative intent had a better OS than patients treated with non-curative procedures (89.2% vs. 6% at 36 months, p < 0.001). Risk factors significantly influencing survival were age at primary BC, interval between BC and PM diagnosis, extra-peritoneal metastases and molecular subtype. Conclusions. The improved outcome in selected cases after a multidisciplinary approach including surgery should lead researchers to regard PMBC patients with greater attention despite their scarce epidemiological impact. Our collective efforts give new information, suggest room for improvement and point to further research for a hitherto poorly studied aspect of metastatic BC.